Scrotum involvement in dermatomyositis - Bagłaj-Oleszczuk, Marta; Hryncewicz-Gwóźdź, Anita; Maj, Joanna; Nockowski, Piotr; Szepietowski, Jacek; Jankowska-Konsur, Alina (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Classic dermatomyositis (DM) is an idiopathic inflammatory myopathy characterized by symmetric, proximal muscle weakness and a wide range of cutaneous findings. Its pathogenesis is not fully understood, however, it is believed that immunogenetic and probably other factors have a significant impact on the manifestation of the disease. Classically, patients exhibit proximal skeletal muscle weakness accompanied by cutaneous symptoms i.e. heliotrope eruption on the eyelids, shawl sign, Gottron sign. Scrotum involvement is an unusual finding in DM. To the best of our knowledge, scrotal ulcerations accompanied by severe pain have been extremely rarely reported as the first dominant manifestation of the disease.